Economics and Ignorance - Scott Scheall (Duke University, Center for the History of Political Economy (CHOPE), 2013)
The present paper considers the relationships – logical and historical – between F.A. Hayek's early business cycle project and his later arguments concerning spontaneous economic orders and the methods appropriate to their investigation. It is a peculiar fact, which familiarity with the contemporary literature on Hayek and the modern Austrian school cannot but make manifest, that those who praise Hayek's business cycle work often disparage or simply ignore his later writings on spontaneous orders and vice versa. If the arguments of the present essay are sound, then these attitudes are largely unjustified.
Keywords: 330; Hayek; business cycle theory; spontaneous orders; economic methodology; ignorance; pretense of knowledge